A novel ultra-low power 7T full adder design using mixed logic. Issue 1 (February 2021) - Siva Kumar, M; Inthiyaz, Syed; Muzammil Parvez, M; Chaithanya Chowdary, P; Bhanu Kiran, M; khan, Pathan Karim
Abstract: The key point is to design and implementation of the full adder which provides high-speed, Power efficiency and leas area with good voltage swing". Where the term 'Novel' indicates that If something is so new, genuine and original that it had never been seen, used or even thought of before, call it is considered as 'novel' and 'Ultra low power' indicates that with the minimal amount of system power is enough for performing the respective operation of its own. In this article, a new High Performance and low power full adder utilizing a distinctive design "Mixed Logic Design" is recommended in implementation. The mixed - logic design combines Modified Gate diffusion input (MGDI) Transmission Gate Logic (TGL), Static CMOS logic, Pass transistor logic(PTL )and various logics which requires the recommended circuit. Full adder is a digital circuit which performs the sum of bits. In many PC's and various kinds of microprocessors, adders are utilized in the ALU. The traditional Complementary Metal Oxide Semiconductor (CMOS) Full adder consisting of 28-Transistors and is built on a traditional Complementary Metal Oxide Semiconductor structure. GDI technique is low power and high-speed design technique where it takes 10 T. Gate Diffusion Input is one of the circuit design logics which occupies less area, simulates with high speed and power-efficient technique. It entails less count of transistors as correlated to traditional Complementary Metal Oxide Semiconductor technology. But the disadvantage with Gate Diffusion Input technique is that it provides an output having poor logic swing after simulation. The Modified-Gate diffusion input (MGDI ) technique rectifies this issue by implementing FA with 8T. But we are implementing another alternative "Mixed logic design" (combining the GDI, CMOS, TGL, etc logics ) and designing the Circuit with least count of transistors and compare with other unique logics which helps them to simulate the circuit in a power-efficient way and time delay.